2021
DOI: 10.1097/cmr.0000000000000785
|View full text |Cite
|
Sign up to set email alerts
|

A novel prognostic biomarker for cutaneous malignant melanoma: red cell distribution width (RDW) to lymphocyte ratio

Abstract: It is well-known that inflammation plays a significant role in cancer formation and prognosis. Both lymphocyte count and red cell distribution width (RDW) has been used to predict prognosis in various cancers as an indicator of inflammation. Yet, the role of RDW-lymphocyte ratio (RLR) in determining prognosis is still unknown. We aimed to determine the prognostic role of RLR in cutaneous malignant melanoma (MM). One hundred fifteen patients with MM were included in the study retrospectively. The relationship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For RDW, RDW-to-lymphocyte ratio was confirmed to be independently associated with the prognosis of cutaneous malignant melanoma, and RDW-to-platelet ratio can be used for the early prediction of cirrhosis and hepatic fibrosis in patients with chronic hepatitis B. 34 , 35 For HDL-C, neutrophils-to-HDL-C ratio had been confirmed as a significant predictor of severe coronary artery stenosis, and triglyceride-to-HDL-C ratio was employed to identify insulin resistance and cardiometabolic risk among children with obesity. 36 , 37 Different from previous studies, the current one was the first attempt to use RDW-to-HDL-C ratio and fully demonstrate its excellent thrombotic predictive value in the field of trauma.…”
Section: Discussionmentioning
confidence: 96%
“…For RDW, RDW-to-lymphocyte ratio was confirmed to be independently associated with the prognosis of cutaneous malignant melanoma, and RDW-to-platelet ratio can be used for the early prediction of cirrhosis and hepatic fibrosis in patients with chronic hepatitis B. 34 , 35 For HDL-C, neutrophils-to-HDL-C ratio had been confirmed as a significant predictor of severe coronary artery stenosis, and triglyceride-to-HDL-C ratio was employed to identify insulin resistance and cardiometabolic risk among children with obesity. 36 , 37 Different from previous studies, the current one was the first attempt to use RDW-to-HDL-C ratio and fully demonstrate its excellent thrombotic predictive value in the field of trauma.…”
Section: Discussionmentioning
confidence: 96%
“…Wu et al demonstrated high sensitivity and specificity of RLR in predicting hepatic impairment in patients with hepatitis E virüs 19 . Hannarici et al discovered the role of RLR as a prognostic marker in cutaneous malignant melanoma 20 . We found that RLR can predict troponin elevation in patients with COP.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest the article entitled 'A novel prognostic biomarker for cutaneous malignant melanoma: red cell distribution width (RDW) to lymphocyte ratio' by Hannarici et al [1] which was recently published in Melanoma Research. I thank the authors for their thoughtful contribution to expanding literature that explores the use of complete blood cell count (CBC) analytes in risk stratification and outcome prediction in melanoma and many other neoplastic and non-neoplastic diseases.…”
mentioning
confidence: 99%
“…Although analytical and preanalytical variables may be particularly problematic for studies that pool data from multiple institutions, preanalytical issues may cause difficulty even in studies conducted in a single institution, because specimen handling conditions may vary among inpatient, outpatient and satellite clinic specimen collection, for example. Although I note that the specimens collected by Hannarici et al [1] originated in a single outpatient environment, it would be important to readers to take into account these potential sources of bias in using the RDW to lymphocyte ratio in clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation